Implementing the Mind Mapping Model to Improve Early Writing Skills Among Students of MIN 11 Pidie - Isra Wahyuni; Iswandi (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research was prompted by the low writing proficiency of Grade I-A students at MIN 11 Pidie, attributed to the prevalence of conventional lecture and assignment methods. This study aims to evaluate the effectiveness of the Mind Mapping model in improving student engagement and learning outcomes within the